Orientation and Mobility (O&M) Efficiency of Persons with Visual Impairment (PVI) in Cameroon Under Varied Circumstances - Ngwa , Suh (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
There are many hypotheses concerning persons with visual impairment. For instance, people generally suppose that “the other senses of PVI are stronger, PVI are less distracted than others, over use of eyesight increases the prognosis of vision loss, PVI are more distrustful, visual impairment is contagious, reading braille with the fingers can only be done by PVI, PVI can distinguish paper money just by touch,” etc., just to mention a few. While some of these suppositions have been empirically investigated and clarified, some of them still remain ambiguous. The objective of this research was to empirically verify three of these presumptions, which are more prevalent amongst PVI themselves in Cameroon, namely: Holding an umbrella under rain impedes PVI orientation and mobility (O&M) efficiency when they are using just the white cane, even if the rain does not hamper their hearing. Wearing a cap while moving with just the white cane, even when it does not hamper hearing, impedes the O&M efficiency of PVI. Walking fast reduces the O&M efficiency of PVI, when they are using just the white cane. It is expected that just holding an umbrella under rain, or wearing a cap while moving with the aid of the white cane, should not affect the O&M efficiency of PVI; while others argue that moving slightly faster instead causes PVI to move in a straight line and should thus be encouraged. It is necessary for such presuppositions to be empirically investigated and either confirmed or nullified in order not to bother if PVI are holding an umbrella under the rain, walking fast, or wearing a cap while moving, with the aid of a white cane, or if these practices should be discouraged.